2017
DOI: 10.1016/j.envpol.2017.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive immunoassay for simultaneous determination of tetrabromobisphenol A bis(2-hydroxyethyl) ether and tetrabromobisphenol A mono(hydroxyethyl) ether: An effective and reliable strategy to estimate the typical tetrabromobisphenol A derivative and byproduct in aquatic environments

Abstract: a b s t r a c tTetrabromobisphenol A bis(2-hydroxyethyl) ether (TBBPA DHEE), as one of the TBBPA derivatives, is frequently applied as a flame retardant. To date, however, little evidence has been gathered regarding its environmental behavior and fate. This is mainly attributed to the lack of an analytical approach available to measure it. Mass spectrometry cannot determine levels of TBBPA DHEE. LC-MS could not ionize TBBPA DHEE to yield enough fragments, while GC-MS could not be applied for the analysis eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…TBBPA is a currently intensively used brominated flame retardant showing widespread environmental and human exposures. Due to its high lipophilicity and persistence, TBBPA could be detected in wastewater [26], fresh surface water [27,28] and sediments [29].…”
Section: Introductionmentioning
confidence: 99%
“…TBBPA is a currently intensively used brominated flame retardant showing widespread environmental and human exposures. Due to its high lipophilicity and persistence, TBBPA could be detected in wastewater [26], fresh surface water [27,28] and sediments [29].…”
Section: Introductionmentioning
confidence: 99%
“…19,23,26,27 However, recent reports have shown that TBBPA-BDBPE is present in abiotic and biotic environmental samples including in the particulate phase of Great Lakes air samples. 5,26,28,29 In the current study, we first suspected that TBBPA-BDBPE was present in fractions of herring gull eggs from Double Island (northern Lake Huron) collected in 2014, where an unknown bromide anion responsive peak was detected in GC-MS(ECNI) mass chromatograms. This unidentified peak matched well with the GC retention time of a TBBPA-BDBPE technical product and was eluted after BDE-209 and DBDPE, which was consistent with a previous report.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Instrument detection limits ranged from 0.12 to 0.19 μg/L, which were generally lower than other methods. Zhang et al reported a new immunoassay for tetrabromobisphenol A bis­(2-hydroxyethyl)­ether and tetrabromobisphenol A mono­(hydroxyethyl ether) . This method helped to overcome some obstacles with LC-MS and GC/MS methods and demonstrated detection limits down to 0.702 μg/L.…”
Section: Brominated and Emerging Flame Retardantsmentioning
confidence: 99%